Abertura econômica e reestruturação produtiva na indústria brasileira: uma análise regional (1985-1997) - Nogueira, Cláudio André Gondim (1999)
The main purpose of this dissertation is to analyze the impacts of the opening process of the brazilian economy over the industry in a regional perspective, trying to identify the main changes of path that had ocurred since then. The results indicate that these impacts were extremely relevant to the reconfiguration of the regional productive structures, as they tried to adapt to a new environrnent, where only competitive firms may survive. This process of structural change of the brazilian industry is somewhat long and slow but, as the empirical evidences show, it has been consolidating and becoming more dynamic as time passes by. Furthermore, the difusion of new technologies and new organizational patterns is becoming more intense and homogeneous among the regions analyzed, showing that they are becoming able to react more properly to new standards of competitiveness. Undoubtly, this result is very interesting because it is surprising to realize that an extremely heterogeneous industrial structure such as the brazilian one is getting able to equalize its capacity to respond and adapt to new contexts.